Thurmond Chatham house, located at 117 N. Stratford Road. - Unknown (Forsyth County Public Library, 2008)
Photo made in the 1920s.
Thurmond Chatham house, located at 117 N. Stratford Road.
Keywords: Forsyth County (N.C.) -- History -- Sources; Forsyth County (N.C.) -- History -- Pictorial works; Digital Forsyth